Biodiversity: An essential natural resource for improving diets and nutrition - Fanzo, Jessica (International Food Policy Research Institute, 2019)
This chapter characterizes the biodiversity on the planet and stresses the importance of biodiversity for agriculture. It then highlights the latest research on the decline in biodiversity and its impact on food supplies, and how biodiversity links to diets. It describes some challenges in ensuring that agrobiodiversity is central to sustainable development. Finally, it identifies the gaps in knowledge that remain and some potential solutions to push biodiversity to the forefront of the 2030 sustainable development agenda.